Pendidikan Agama Anak dalam Keluarga Qur’an Surah Lukman Ayat 12-19: Studi Komparatif Tafsir Ibnu Katsir dan Al-Misbah - Yanti, Herina (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Cultivating religious values from an early age to children starts in the household as the first education for a child, so parents as first educators must prepare themselves and prepare the religious education material for their children. A child's sense of religion will not grow by itself, without us cultivating it from the start and setting an example in the family’s daily routine. The type of research conducted by the author is library research by comparing the interpretations of Ibnu Katsir and M. Quraish Shihab. The results of the study show that the interpretation of Ibnu Katsir and M. Quraish Shihab is almost the same in interpreting surah Lukman verses 12-19. The difference is that M. Quraish Shihab translated the verses in detail with the meaning of the words, while Ibnu Katsir translated by dividing the verse and adding verses and hadiths that are connected to each other. The core of Surah Lukman verses 12-19 are gratitude, monotheistic teachings about the prohibition of shirk, serving both parents, establishing prayer, doing good and preventing bad actions, prohibiting being arrogant, being modest in life, and being soft and gentle.